2010
DOI: 10.1073/pnas.1002690107
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and specific interaction between synaptic NR2-NMDA receptor and PDZ proteins

Abstract: The relative content of NR2 subunits in the NMDA receptor confers specific signaling properties and plasticity to synapses. However, the mechanisms that dynamically govern the retention of synaptic NMDARs, in particular 2A-NMDARs, remain poorly understood. Here, we investigate the dynamic interaction between NR2 C termini and proteins containing PSD-95/Discs-large/ZO-1 homology (PDZ) scaffold proteins at the single molecule level by using highresolution imaging. We report that a biomimetic divalent competing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 37 publications
8
87
0
Order By: Relevance
“…Following the exocytosis of pH-NR1, the pHluorin tag will be exposed to the extracellular solution with pH 7.4 and its fluorescence will dramatically increase. Previous studies showed that neither pHluorin nor EGFP fluorescent tag at the N terminus of NR1 affected its trafficking in neurons (26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the exocytosis of pH-NR1, the pHluorin tag will be exposed to the extracellular solution with pH 7.4 and its fluorescence will dramatically increase. Previous studies showed that neither pHluorin nor EGFP fluorescent tag at the N terminus of NR1 affected its trafficking in neurons (26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Following the exocytosis of pH-NR1, the pHluorin tag will be exposed to the extracellular solution with pH 7.4 and its fluorescence will dramatically increase. Previous studies showed that neither pHluorin nor EGFP fluorescent tag at the N terminus of NR1 affected its trafficking in neurons (26)(27)(28).To visualize the exocytosis of NR1, dissociated hippocampal neurons grown on glass coverslips were cotransfected with pH-NR1 and untagged NR2A subunit to form NMDA receptor complexes, and imaged 24-48 h after transfection. Following the photobleaching of preexisting fluorescence on the plasma membrane Significance NMDA receptors are ionotropic glutamate receptors and crucial for excitatory synaptic transmissions in the brain.…”
mentioning
confidence: 99%
“…Based on these findings, one may predict that favoring the presence of perisynaptic NMDAR in the spine area would increase their potential binding to D1R and thereby modulate the size of D1R clusters. To address this question, we artificially increased the amount of perisynaptic NMDAR by blocking their synaptic retention with a biomimetic ligand (TAT-[N2A 15 ], 10 μM, 20 min) that prevents their Cterminal interaction with cytosolic PDZ domain-containing proteins (22). Strikingly, this treatment resulted in a rapid and significant increase in D1R cluster intensity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They were NR2A(1381-1390), RCPSD-PYKHS, termed SH3, and corresponded to the amino acid sequence around the SH3 binding domain; SH3 scrambled, DSYSRPHCKP; NR2A(1450 -1464), NRRVYKKMPSIESDV, termed PDZ, and corresponded to the amino acid sequence at the C-terminal ESDV domain and the same as used previously (18), and PDZ scrambled, KRSMNIVEKDPVRYS.…”
Section: Peptidesmentioning
confidence: 99%